2015
DOI: 10.1104/pp.15.01699
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Transpiration Barrier in the Epi- and Intracuticular Waxes of Eight Plant Species: Water Transport Resistances Are Associated with Fatty Acyl Rather Than Alicyclic Components

Abstract: Plant cuticular waxes play a crucial role in limiting nonstomatal water loss. The goal of this study was to localize the transpiration barrier within the layered structure of cuticles of eight selected plant species and to put its physiological function into context with the chemical composition of the intracuticular and epicuticular wax layers. Four plant species (Tetrastigma voinierianum, Oreopanax guatemalensis, Monstera deliciosa, and Schefflera elegantissima) contained only very-long-chain fatty acid (VLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(187 citation statements)
references
References 51 publications
14
173
0
Order By: Relevance
“…To the authors' knowledge, similar studies testing the effects of VLCA and cyclic wax fractions on organic solute permeability of cuticles have not been reported to date. The results here, however, agree with the finding by Jetter and Riederer that in eight species, the fatty acyl wax fraction was associated with cuticular water permeability . Another study proposed the hypothesis that cyclic compounds in tomato fruit cuticles do not constitute the permeation barrier to water …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To the authors' knowledge, similar studies testing the effects of VLCA and cyclic wax fractions on organic solute permeability of cuticles have not been reported to date. The results here, however, agree with the finding by Jetter and Riederer that in eight species, the fatty acyl wax fraction was associated with cuticular water permeability . Another study proposed the hypothesis that cyclic compounds in tomato fruit cuticles do not constitute the permeation barrier to water …”
Section: Discussionsupporting
confidence: 91%
“…The waxes associated with the plant cuticle impregnate the cutin matrix (intracuticular waxes) and are deposited on the outer surface as a thin film (epicuticular waxes), sometimes together with epicuticular wax crystals . Previous studies have demonstrated that the epicuticular wax of the plant species investigated consisted of VLCAs, whereas the cyclic fraction was located exclusively in the interior of the cutin matrix . Treating the intact adaxial surface of leaves of P. laurocerasus with methanol did not release any triterpenoids, proving that the cyclic compounds are located in the inner layers of the cuticle and are effectively shielded from the extractive action of methanol by a superficial layer of VLCAs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waxes are embedded into the polymer matrix and deposited onto its surface (Buschhaus & Jetter, 2011), to protect the tissue against adverse abiotic and biotic conditions (Jetter & Riederer, 2016;MĂźller, 2006;Reina-Pinto & Yephremov, 2009). Wax compositions and transpiration barrier properties vary widely between species (Jetter & Riederer, 2016), likely due to fine-tuned differences in the underlying biosynthetic machineries.…”
mentioning
confidence: 99%
“…might increase if the wax layers are degraded. Jetter and Riederer 2016 reported that the sealing properties of the cuticular were not correlated with the absolute wax amount and thickness of wax layers, but it is maintained by the existence of the layer containing very long chain fatty acid. Barnes et al 1988 investigated the effect of O 3 fumigation on the condition of the epicuticular wax of Norway spruce using scanning electron microscopy SEM .…”
Section: Figmentioning
confidence: 99%